2020
DOI: 10.1002/phar.2486
|View full text |Cite
|
Sign up to set email alerts
|

First‐Dose Vancomycin Pharmacokinetics Versus Empiric Dosing on Area‐Under‐the‐Curve Target Attainment in Critically Ill Patients

Abstract: Background Early attainment of target area under the curve (AUC) to minimum inhibitory concentration (MIC) ratios have been associated with clinical success, as well as lower incidence of acute kidney injury (AKI), in patients receiving vancomycin for methicillin-resistant Staphylococcus aureus (MRSA). Critically ill patients are particularly vulnerable to poor outcomes from infection and face multiple risk factors for AKI, thus early precision dosing of vancomycin is vital in this population. We hypothesized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
(55 reference statements)
1
8
0
Order By: Relevance
“…Several published reports suggested that vancomycin exhibits longer distribution phase [ 17 , 60 , 61 ] and using one compartment approach may result in inaccurate PK estimations. Flannery et al [ 21 ] reported that PTA at steady state was 58.6% with one compartment approach, which is also in accordance with observations from Ackerman et al [ 62 ], suggesting that the one-compartment model may not be sufficient to predict vancomycin exposure.…”
Section: Discussionsupporting
confidence: 69%
See 4 more Smart Citations
“…Several published reports suggested that vancomycin exhibits longer distribution phase [ 17 , 60 , 61 ] and using one compartment approach may result in inaccurate PK estimations. Flannery et al [ 21 ] reported that PTA at steady state was 58.6% with one compartment approach, which is also in accordance with observations from Ackerman et al [ 62 ], suggesting that the one-compartment model may not be sufficient to predict vancomycin exposure.…”
Section: Discussionsupporting
confidence: 69%
“…Method 3 is an adopted approach from Flannery et al [ 21 ], which recommends collecting two samples. One sample at 2.5 h (1–2 h after the end of infusion), and the other level at 11.5 h (trough level) are collected.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations